1994
DOI: 10.1136/gut.35.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Association between Meckel's diverticulum and Crohn's disease: a retrospective review.

Abstract: The operation notes and pathology records of 294 consecutive patients who had right hemicolectomy for Crohn's disease were reviewed. A Meckel's diverticulum was found in 17 (5 8%) ofthese patients, 2-3 times the expected rate in the general population. At least 50% of diverticula in the normal population contain heterotopic mucosa, but none was found in those diverticula that were examined from this group. The increased prevalence of Meckel's diverticulum in patients with Crohn's disease confirms previous anec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 7 publications
2
32
0
1
Order By: Relevance
“…Prompted by anecdotal reports of an increased incidence of Meckel's diverticulum in Crohn's disease, Andreyev et al [1], on the basis of a review of 294 consecutive right hemicolectomy specimens, found an incidence of 5.4% in patients with Crohn's disease. They concluded that this represented a two-to threefold increase in the incidence of Meckel's diverticulum over the general population [1].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prompted by anecdotal reports of an increased incidence of Meckel's diverticulum in Crohn's disease, Andreyev et al [1], on the basis of a review of 294 consecutive right hemicolectomy specimens, found an incidence of 5.4% in patients with Crohn's disease. They concluded that this represented a two-to threefold increase in the incidence of Meckel's diverticulum over the general population [1].…”
Section: Discussionmentioning
confidence: 98%
“…One large study suggested an increased incidence of Meckel's diverticulum in patients with the disease [1], and another refuted this assertion [2]. Although clearly there are cases of Meckel's diverticulum found at the time of operation for Crohn's disease, including the assertion that an acid-secreting diverticulum may mimic the disease [3], it is rare for the diverticulum to be involved with Crohn's disease [4].…”
Section: Introductionmentioning
confidence: 98%
“…The normal colonoscopy ruled out inflammatory bowel disease of the large bowel. Meckel's diverticulum is thought to occur much more often in association with Crohn's disease [9]. Endoscopy was not performed on our patient so we could not exclude Crohn's disease involving the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recorded in patients with CD, with some authors reporting an incidence of 6% to 18.5% (8). In their review of 294 patients with CD, Andreyev et al (9) found the prevalence of MD to be up to 3 times above that of the general population. However, Freeman (5) recently found 877 patients with CD, among whom 10 (about 1%) had a diagnosis of MD, including 6 men and 4 women, with a prevalence similar to the general population.…”
Section: Discussionmentioning
confidence: 99%